2020
DOI: 10.3390/ijms21186692
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CDC20 Increases Radiosensitivity through Mcl-1/p-Chk1-Mediated DNA Damage and Apoptosis in Tumor Cells

Abstract: Radiotherapy is an important modality for the local control of human cancers, but the radioresistance induced by aberrant apoptotic signaling is a hallmark of cancers. Restoring the aberrant apoptotic pathways is an emerging strategy for cancer radiotherapy. In this study, we determined that targeting cell division cycle 20 (CDC20) radiosensitized colorectal cancer (CRC) cells through mitochondrial-dependent apoptotic signaling. CDC20 was overexpressed in CRC cells and upregulated after radiation. Inhibiting C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…CDC20 has been also involved in the apoptotic response, by regulating phosphatidylcholine (PC) cycle [ 102 , 103 ] and balancing the activity of anti-apoptotic factors, as MCL-1 [ 104 108 ] and BCL-2 [ 108 , 109 ], and pro-apoptotic factors, as BIM [ 110 ] (Fig. 5 A-D).…”
Section: Main Textmentioning
confidence: 99%
“…CDC20 has been also involved in the apoptotic response, by regulating phosphatidylcholine (PC) cycle [ 102 , 103 ] and balancing the activity of anti-apoptotic factors, as MCL-1 [ 104 108 ] and BCL-2 [ 108 , 109 ], and pro-apoptotic factors, as BIM [ 110 ] (Fig. 5 A-D).…”
Section: Main Textmentioning
confidence: 99%
“…Importantly, recent studies have reported a group of specific inhibitors of Cdc20 in the pre-clinical model of different kinds of cancer ( 27 , 28 ). The tumor xenografts in immune-competent mice with or without CDC20 knockdown were shown to have a dramatic shrinkage in tumor volume, compared with the knockdown of CDC20 in the immune-deficient mice model as previous reproted ( 29 ). As CDC20 expression correlated with CAFs and MDSCs, it is proposed that the anti-tumor effects of targeting Cdc20 could be augmented by the immune system.…”
Section: Discussionmentioning
confidence: 75%
“…Min Shi et al found that CDC20 played a crucial role in the development of hepatocellular carcinoma by regulating the PHD3 protein [ 26 ]. Besides, Yang Gao et al found that targeting CDC20 sensitized colorectal cancer cells to radiotherapy through mitochondrial-dependent apoptotic signaling [ 27 ]. Qin Zhang et al found that CDC20 combined with CD44 or β-catenin could serve as an important indicator for the prognosis of patients with prostate cancer [ 28 ].…”
Section: Discussionmentioning
confidence: 99%